Pembahasan Rancangan Anggaran Pendapatan dan Belanja Daerah Dalam Percepatan Pembangunan Infrastruktur Jalan Tahun Anggaran 2013 - RAHMATILLAH, RANI; KHAIRANI, TUTI (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Drafting the Regional Budget authority is a form of attention from the local government as well Indragiri Hulu in addressing road infrastructure damage. The research was conducted at Parliament's office and the Office of Local Government participating Indragiri Hulu discuss RAPBD road infrastructure. The purpose of this studywas to determine the discussion draft Regional Budget (RAPBD) to accelerate the development of road infrastructure Indragiri Hulu fiscal year 2013. This research uses descriptive qualitative method. Data were obtained from the interview data, documentary studies, and field observations. Informants in this study are related parties to the discussion RAPBD road infrastructure using the snowball method. The results showed that the fund will determine the achievement of the development of road infrastructure. Lack of budget for the construction of roads lead to road infrastructure development level is only about 3-5% every year. Additionally musrenbang activity only partially understood by the public. Though musrenbang very important activity as the voice of the people.Keywords: Planning, Budgeting, Local Government